Pravice manjšin in jezikovne pravice v medijih v Republiki Sloveniji in v tujini - Žurej, Jurij (Revus (Ljubljana), 2004)
In Slovenia and abroad there are a large number of language-related regulations that affect the shape of the broadcasting media and therefore have an impact on the life of persons belonging to minorities. Language has been and remains an important instrument in State-building and maintenance. In this context, requirements have also been put in place to accommodate national minorities. In this article, the author deals with basic principles of protecting minority and language-related rights in broadcasting in the Republic of Slovenia. The article also presents interesting solutions in the legislation and practice of other countries. It points out questions of official recognition of specific languages, promotion of official/state language(s), language quotas, translation requirements accommodation/promotionof minority languages, the special role of public service broadcasting, observations concerning licensing, cross-border dimensions and similar questions related to the topic.
Keywords: človekove pravice; jezikovne pravice; mednarodne primerjave; množični mediji; narodne manjšine; pravice manjšin; pravno varstvo; Slovenija